On Model-Independent Analyses of Elastic Hadron Scattering - S.D. Campos (Brazilian Journal of Physics, 2007)
By means of an almost model-independent parametrization for the elastic hadron-hadron amplitude, as afunction of the energy and the momentum transfer, we obtain good descriptions of the physical quantities thatcharacterize elastic proton-proton and antiproton-proton scattering (total cross section, r parameter and differentialcross section). The parametrization is inferred on empirical grounds and selected according to high energytheorems and limits from axiomatic quantum field theory. Based on the predictive character of the approach wepresent predictions for the above physical quantities at the Brookhaven RHIC, Fermilab Tevatron and CERNLHC energies.